A Cracked Public Administration in Peru: How “Vacunagate” Has Shaken the Foundations of an Already Damaged Society (2022)
While crises are ubiquitous in Latin America, due to its geographical characteristics as well as its turbulent business environment, countries such as Peru have also extreme rates of corruption and deep institutional weakness. These factors, taken together, undermine any attempt of national governments or society’s collective efforts towards achieving sustainability. This paper aims to analyze the “Vacunagate” scandal that occurred in Peru during the first negotiations of the vaccination process against COVID-19, using a case study method, and focusing our discussion from the Agency Theory as well as from leadership and institutional perspectives. The results of the analysis emphasize how the “Vacunagate” event generated relevant constraints towards the achievement of the SDG 16, and its specific targets related to provide justice for all, deal with organized crime, reduce corruption, and create accountable institutions. In addition, the study provides insights and implications for organizations in Peru that would have to operate under a turbulent business environment, considering a business-as-usual corruption and a weak institutional context.